Longitudinal study of neurofibromatosis 1 associated plexiform neurofibromas. Issue 2 (17th October 2008) - Tucker, T; Friedman, J M; Friedrich, R E; Wenzel, R; Fünsterer, C; Mautner, V-F
Abstract : Background: Plexiform neurofibromas are benign tumours that occur in more than half of people with neurofibromatosis 1 (NF1). These tumours can cause serious complications and can also progress to malignant peripheral nerve sheath tumours (MPNSTs), one of the leading causes of death among NF1 patients. Plexiform neurofibromas are clinically heterogeneous, and knowledge of their natural history is limited. In order to characterise the growth of plexiform neurofibromas better, we performed serial magnetic resonance imaging (MRI) in NF1 patients with such tumours. Methods: MRI was done on 44 plexiform neurofibromas in 34 NF1 patients (median age 10 years; range 1–47 years). Each tumour was measured in two dimensions from the MRI scan, and the area and growth rate were calculated. The median length of follow-up was 6 years, with an average interval of 3 years between scans. Results: 36 tumours remained stable in size throughout the period of follow-up. 8 tumours increased in size; all occurred in patients who were under 21 years of age when first studied. The single exception was a man who developed rapid tumour growth and pain in a plexiform neurofibroma that had been followed for 10 years. Biopsy showed the presence of an MPNST. Conclusion: Longitudinal MRI is a valuable means of monitoring the growth of plexiform neurofibromas in individuals with NF1.